High mortality in cervical fracture with ankylosing spondylitis : case reports - Goh, Kian Liang; Zakaria@Mohamad, Zamzuri; Mohd Amin, Azril; Awang, Mohd Shukrimi; Mohd Yusof, Nazri (2011)
Ankylosing spondylitis is a systemic inflammatory disease which may predispose the cervical spine to fracture, subluxation or dislocation. High mortality and morbidity has been reported mainly due to neurological deficit, respiratory failure and sepsis. We report two patients with ankylosing spondylitis presenting with cervical fracture after motor vehicle accident who succumbed to respiratory failure.